2022
DOI: 10.3389/fpls.2022.986034
|View full text |Cite
|
Sign up to set email alerts
|

The divergent vertical pattern and assembly of soil bacterial and fungal communities in response to short-term warming in an alpine peatland

Abstract: Soil microbial communities are crucial in ecosystem-level decomposition and nutrient cycling processes and are sensitive to climate change in peatlands. However, the response of the vertical distribution of microbial communities to warming remains unclear in the alpine peatland. In this study, we examined the effects of warming on the vertical pattern and assembly of soil bacterial and fungal communities across three soil layers (0–10, 10–20, and 20–30 cm) in the Zoige alpine peatland under a warming treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Assembly mechanisms are closely linked to changes in community structure, diversity, and the ecological functions they support ( Fukami, 2015 ). This phenomenon has been extensively studied in various ecosystems, such as soil microbes ( Wang et al., 2022 ; Cao et al., 2023 ), bacterioplankton ( Dai et al., 2017 ), intertidal communities ( Loke and Chisholm, 2023 ), and plants ( Peter and Harrington, 2018 ; Tanunchai et al., 2023 ). Assembly processes are influenced by various environmental factors, with community turnover cycles limiting exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Assembly mechanisms are closely linked to changes in community structure, diversity, and the ecological functions they support ( Fukami, 2015 ). This phenomenon has been extensively studied in various ecosystems, such as soil microbes ( Wang et al., 2022 ; Cao et al., 2023 ), bacterioplankton ( Dai et al., 2017 ), intertidal communities ( Loke and Chisholm, 2023 ), and plants ( Peter and Harrington, 2018 ; Tanunchai et al., 2023 ). Assembly processes are influenced by various environmental factors, with community turnover cycles limiting exploration.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the fungal communities within the mycorrhizal and soil ecological niches were directly or indirectly affected by abiotic factors. Both mycorrhizal and soil fungal communities can be directly or indirectly influenced by abiotic factors [58][59][60][61][62]. Soil serves as the immediate habitat for soil microbes and, as such, its physical and chemical properties directly impact the resident microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that short-term warming treatments in alpine peatlands did not result in significant changes in the α diversity of fungal communities. (Wang et al 2022).…”
Section: Effects Of Night-time Warming and Different Fertilization Re...mentioning
confidence: 99%